Over-Expression of Biomolecules Inphosphatidylinositol-3-Kinaseiakt Signaling Pathway Inbreast Cancer - Loh, Hui Woon (2005)
Breast cancer is the leading cancer among women in Malaysia. Genetics, experimental and epidemiological data suggest that breast cancer develops from complex interaction between inherited susceptibility and environmental factors. Accumulating evidence suggests that the PI3WAkt signaling pathways play a causative role in tumorigenesis of breast cancer. By employing the immunohistochemical method, the expression of several key regulators or related biomolecules of the PI3WAkt signaling pathways in 43 archived formalin fixed, paraffin embedded tissues of surgically resected breast carcinoma specimens from 1999 to 2002, were studied. A hnctional assay was performed to determine the expression of Akt related molecules when treated with SDF-la recombinant protein. iii The results showed that: 1) The expression rates in tumour tissue of ERa, ERP, cerbB2, p-~ktm08p-, p - ~ ~ ~ S S1D3F-61 ,a nd Ki67 were 25.6%, 4.7%, 5 1.2%, 81.4%, 48.8%, 67.4%, 93.0% and 26.8%, respectively. In contrast, in the apparently normal adjacent tissue, the expression rates of these molecules were 23.1%, 53.8%, 0%, 7.7%, 7.7%, 53.8%, 92.3% and 15.4%, respectively. 2) Correlation of biomolecules with tumour tissues and apparently normal adjacent tissues was seen in the following biomolecules: ERP (p=0.001), c-erbB2 (p<0.001), p-~ktT30(p8= <0.001) and Ki67 (p=<0.001). 3) In tumour tissue, significant correlation was found between ERP with p - (~p=0.00~4), p -~~ kSt47 3 with p-BAD (p=0.006), c-erbB2 with p-Akt and Ki67 (p=0.014 and p=0.000 respectively) and c-erbB2 with SDF-1 (p=0.047). In the apparently normal adjacent tissue, a significant correlation was found between ERa with p - ~ ~ ~ S ('p3=06.0 42), ERP with p-Akt S473 and p-BAD (p=0.009 and p=O.OOl respectively), and c-erbB2 with p - ~ kTt3 08 (p=0.042). Our study also showed that SDF-la protein had a different effect on the expression of biomolecules, namely p-AktT308p, - AktS473a nd p - ~ ~ ~ S ' I3n 6th. i s hnctional assay, we found that SDF-la could possible induce cell survival by inducing phosphorylation of Akt at Thr308 and Ser473 as well as phosphorylation of BAD at Ser136 which are anti-apoptotic signals. Similar patterns were observed with all three cell lines, namely MCF-7, MDA-MB-231 and MCFIOA but the level of expression differed from each other. This study had provided three important information for researchers and clinicians in terms of: (1) evidence of the involvement of the SDF-la in the PI3WAkt signaling pathway in breast carcinoma tumourigenesis with detection of p-Akt. 2) For the first